How to Thrive in Professional Practice: A Self-care Handbook - Mordue, Stephen J; Watson, Lisa; Hunter, Steph (Routledge, 2020)
This engaging book pulls together the individual strains of self-care, spirituality and common sense. It is a one-stop 'bible' to give social workers and other professionals an uncomplicated, easy to read resource that empowers them to manage and maintain their well-being through personal responsibility and self-care. The world today is fast paced and societal expectations for impeccable service are high. We cannot always alter the demands of our professional or personal lives, but by actively pursuing well-being we can enhance skills to support open discussion in supervision (or in personal reflection) so that individuals (and organisations) can successfully rise to meet challenges head on and reduce the risks associated with burnout. Building on the authors' years of personal experience, this book Brings together everything professionals need for their own self-care through a range of practical activities Gives you tried and tested self-care ideas backed by the latest research Allows you as professionals to take a holistic approach to a range of subjects that people usually explore in isolation.